Pelatihan Uji Pasar Green Body Parfume Dengan Metode Kuesioner di SMK Bina Insan Mandiri - Chandra, Agung; Novrisal, Dimas; Rochmad, Imbuh (Unity Academy, 2025)
Thie aim of this training is to transfer the knowledge to senior high school student in testing the market systematically before launching the product. The students were taught how to make the questionnaire effectively, to collect data from the potential customers and to analyze the survey results to understand the market preferences. Methods used in this training are theory explanation, practicing in making and distributing the questionnaire, and data analysis.. The result showed that questionnaire methods for testing the market which collected from 39 respondents was the fittest market strategy is social media that reflected from most respondents who chose it. The target output was expected that this training was not only to transfer theoretical knowledge but also the skill how to make and to distribute questionnaire to respondents could be implemented in the real world, and the students was motivated to become innovative and analytical entrepreneur.